What is the standard form of y=(-2x+3)(-x-1)?

felpillauvc

felpillauvc

Answered

2022-02-01

What is the standard form of y=(-2x+3)(-x-1)?

Answer & Explanation

Evie French

Evie French

Expert

2022-02-02Added 18 answers

Explanation:
Given:
y=(-2x+3)(-x-1)
The standard form for a quadratic equation is:
y=ax2+bx+c
To convert the given equation to standard form, multiply the two binomials using the FOIL method.
y=(-2x*-x)+(-2x*-1)+(3*-x)+(3*-1)
y=2x2+2x3x3
Combine like terms.
y=2x2x3

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?